Tunable interface states in locally resonant acoustic chains with inerters - Milan Cajic (ENOC2022-Book of abstracts, 2022)
In this work, we study locally resonant acoustic chains with inerters. Topological properties are investigated on the exampleof one-dimensional chain with diatomic mass-in-mass unit cells based on the band structure and eigenstate analysis. The existence ofinterface modes in finite chains is confirmed through natural frequencies and frequency response function analysis. Tuning of interfacemodes due to introduced inertia amplification effect is observed and investigated in details.